Enhancing Global Visibility of Museum Keris Nusantara Surakarta Through Digital Storytelling - Fauzi Ichwani; Asa Sheila Amelia (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study explores how digital media based storytelling can enhance the global visibility and cultural relevance of Museum Keris Nusantara Surakarta. As one of Indonesia’s most prominent heritage institutions dedicated to the art and philosophy of the keris, the museum holds extensive collections that reflect the artistic, historical, and symbolic values of Javanese weaponry and craftsmanship. However, in an increasingly digital society, traditional promotional methods are no longer sufficient to attract international audiences. This research investigates how the integration of digital storytelling, including social media narratives, virtual exhibitions, short-form videos, and interactive online content, can strengthen the museum’s branding and engagement beyond national boundaries. Using a qualitative descriptive approach, the study analyzes digital media strategies adopted by leading cultural institutions and evaluates their applicability to Museum Keris Surakarta. Data were collected through interviews, documentation, and observational assessments of existing digital content. The findings indicate that compelling storytelling embedded within digital formats such as narrative-driven visuals, behind-the-scenes forging processes, empu (master smith) personal stories, and thematic interpretations of keris symbolism significantly increases user engagement and cross-cultural appreciation. Moreover, platforms like Instagram, YouTube, and TikTok are identified as highly effective for reaching younger global audiences, while web-based virtual tours offer immersive experiences for international visitors unable to visit physically. The study concludes that digital storytelling is not merely a promotional tool but a strategic instrument for cultural diplomacy. By presenting keris narratives in accessible and emotionally resonant formats, Museum Keris Nusantara Surakarta can cultivate greater global recognition, support heritage preservation, and strengthen its position within the international cultural landscape. The findings highlight the need for museums to adopt innovative digital practices to remain relevant and competitive in the era of global digital communication. Keywords: digital storytelling, museum keris Surakarta, cultural heritage, virtual exhibition, global audience engagement